Influence of wind direction and speed on the transport of particle-bound PAHs in a roadway environment - Kim, Kyung Hwan; Lee, Seung-Bok; Woo, Daekwang; Bae, Gwi-Nam (TURKISH NATL COMMITTEE AIR POLLUTION RES & CONTROL-TUNCAP, 2015)
The influence of wind direction and speed on the transport of vehicular air pollutants was investigated using a mobile laboratory in an urban area. We considered three spatial scales covering typical transport phenomena observed in urban areas: micro-scale (a few tens of meters), middle-scale (a few hundred meters) and neighborhood-scale (a few kilometers). Particle-bound polycyclic aromatic hydrocarbons (PAHs) were selected as an indicator of vehicle emissions in the roadway environment. From the microscale measurements, we found a significant difference in the concentration of particle-bound PAHs within a small spatial area, on a two-way road, due to the effect of wind direction when the prevailing wind direction was constant. In the middle-scale experiments, an exponential decrease in the concentration of particle-bound PAHs was observed with distance from the intersection in the direction of the prevailing wind, which is consistent with the results of previous studies. The concentration of particle-bound PAHs near the road was similar to 10 times higher than that at 200 m away from the road due to the significantly low background concentration, indicating that particle-bound PAHs are a good indicator of vehicle emissions in a roadway environment. From long-distance (similar to 15 km) traveling measurements made over 14 days, we found that the average concentration of particle-bound PAHs on the road decreased as the prevailing wind speed increased at the neighborhood-scale, when the wind speed was higher than 2.0 m/s. This analysis, over three spatial scales, will be helpful in understanding the effect of wind on air pollution in a roadway environment in urban areas. Copyright (c) 2015 Turkish National Committee for Air Pollution Research and Control. Production and hosting by Elsevier B.V. All rights reserved.
Keywords: POLYCYCLIC AROMATIC-HYDROCARBONS; AIR-POLLUTION IMPACTS; ULTRAFINE PARTICLES; VEHICLE EMISSIONS; SIZE DISTRIBUTION; PARTICULATE MATTER; LOS-ANGELES; WIDE AREA; URBAN; PM2.5